Analisis Kualitas Limbah Cair Peternakan Ayam di Kabupaten Pangkajene Kepulauan - Hildayani, Hildayani (Journal Gallus Gallus, 2024)
Wastewater from chicken farms can cause a major risk to environmental pollution. Waste management needs to be carried out in chicken farming facilities because it ensures environmental protection, human health, and the quality of life of workers and communities living near chicken farming facilities. This study was conducted to analyze the quality of chicken farm wastewater discharge, namely broiler chicken breeding on farms based on chemical parameters, in addition it also aims to determine the characteristics of chicken farm wastewater. Wastewater samples were taken from the inlet and outlet of the Waste Treatment Plant (IPAL) at one of the chicken farms in Pangkep Regency. These samples were then taken to the laboratory to test the characteristics of the wastewater. Analysis of the quality of chicken farm wastewater, namely broiler chicken breeding in Pangkep Regency, was carried out using the Regulation of the Minister of Environment Number 5 of 2014 on Wastewater Quality Standards. The results of laboratory tests showed that the characteristics of chicken farm wastewater were Temperature 30.6˚; pH 7.24; Dissolved Solids (TDS) 665.9 mg/L; Suspended Solids (TSS) 48 mg/L; Chemical Oxygen Demand (COD) 277.81 mg/L and Biological Oxygen Demand (BOD) 101.32 mg/L; Nitrite 0.017 mg/L; Nitrate 4.79 mg/L. In addition, there was a significant decrease in value after wastewater treatment at the IPAL so that the value of each parameter could meet the established quality standards.